E-learning in the Department of Library Science of UIN Alauddin Makassar Based on Claroline - Mathar, Taufiq; Akbar, A. Khaidir; Arifin, Nur (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2020)
Background of the study: Since established in 1999, the Department of Library Science of Universitas Islam Negeri (UIN) Alauddin Makassar has been teaching its degree students throughout conventional way of teaching, in which whiteboards and classrooms are still mostly used as learning media till current days. The department challenges with the growing education technology, media such as e-learning.Purpose: This paper is aimed to describe the strategic planning to build and implement an e-learning in the department and to configure e-learning software called Claroline.Method: The data were gathered by discussing with all lecturers and several students as the basic sources to plan and build e-learning.Findings: As the research findings, Panrita 4.0 was determined as its e-learning’s name in order to make the engaged users (lecturers and students) be more familiar with.Conclusion: In addition, the study highlighted challenges faced by most lecturers in implementing such learning media although trainings have been conducted. However, most students were more enjoy learning with Panrita 4.0, even though it was their first experience dealing with such media.